Social Innovation and University Intellectual Property: Insights from the UK and Mexico - McDonagh, L.; Bonadio, E.; Alba Betancourt, A. (European Intellectual Property Review, 2020)
University intellectual property policies, and the accompanying strategies for incubation of IP via licensing and spin outs, have not received much analysis from academic lawyers. Moreover, despite the success of universities in the UK at generating income from IP, not much is known about how transferable this success is when considered in the light of a rapidly growing middle-income developing economy such as Mexico’s. In this article we analyse critically some of the key tenets of IP policies at universities in the UK to identify what the key legal principles underpinning university innovation are. We further consider the potential application of these principles in Mexico, where so far only a limited number of universities have developed IP policies and strategies in line with the incubator model. We explain how universities in Mexico could implement these research findings in their own IP policies. We further note that the mere provision of an IP policy is not a panacea – on its own it is insufficient for ensuring technology transfer and it may even encourage unnecessary patenting. Further investment in infrastructure and in establishing a culture of incubation and entrepreneurship is also required.
Keywords: Amérique latine; Europe; Libre accès; Propriété intellectuelle; UK

Social Innovation and University Intellectual Property: Insights from the UK and Mexico - McDonagh, L.; Bonadio, E.; Alba Betancourt, A. (European Intellectual Property Review, 2020)
University intellectual property policies, and the accompanying strategies for incubation of IP via licensing and spin outs, have not received much analysis from academic lawyers. Moreover, despite the success of universities in the UK at generating income from IP, not much is known about how transferable this success is when considered in the light of a rapidly growing middle-income developing economy such as Mexico’s. In this article we analyse critically some of the key tenets of IP policies at universities in the UK to identify what the key legal principles underpinning university innovation are. We further consider the potential application of these principles in Mexico, where so far only a limited number of universities have developed IP policies and strategies in line with the incubator model. We explain how universities in Mexico could implement these research findings in their own IP policies. We further note that the mere provision of an IP policy is not a panacea – on its own it is insufficient for ensuring technology transfer and it may even encourage unnecessary patenting. Further investment in infrastructure and in establishing a culture of incubation and entrepreneurship is also required.
Keywords: Amérique latine; Europe; Libre accès; Propriété intellectuelle; UK